2021
DOI: 10.1038/s41598-021-00593-z
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned soils reveal plant-selected microbial communities that impact plant drought response

Abstract: Rhizobacterial communities can contribute to plant trait expression and performance, including plant tolerance against abiotic stresses such as drought. The conditioning of microbial communities related to disease resistance over generations has been shown to develop suppressive soils which aid in plant defense responses. Here, we applied this concept for the development of drought resistant soils. We hypothesized that soils conditioned under severe drought stress and tomato cultivation over two generations, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In recent years, evidence has been mounting that upon perceiving environmental stress, plants actively shape their microbiome to recruit microbes that help alleviate such harmful conditions 18 , as has been reported for plants responding to nutrient deficiency 40,41 , drought [42][43][44] or salinity 45 , but also to stress caused by microbial pathogens 13,14,20,46,47 . The disease-induced recruitment and buildup of beneficial microbes is thought to result in the creation of disease-suppressive soils [18][19][20][21]48,49 .…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, evidence has been mounting that upon perceiving environmental stress, plants actively shape their microbiome to recruit microbes that help alleviate such harmful conditions 18 , as has been reported for plants responding to nutrient deficiency 40,41 , drought [42][43][44] or salinity 45 , but also to stress caused by microbial pathogens 13,14,20,46,47 . The disease-induced recruitment and buildup of beneficial microbes is thought to result in the creation of disease-suppressive soils [18][19][20][21]48,49 .…”
Section: Discussionmentioning
confidence: 98%
“…By providing a diverse carbon‐rich environment, plant species harbor a distinctive microbial community in their rhizosphere which, in turn, confers several fitness advantages to the plant host, shaping their assemblage and modulating their beneficial traits (Badri & Vivanco, 2009; Mönchgesang et al, 2016; Trivedi et al, 2020). In addition, root exudate‐derived metabolites act as important mediators structuring a stress‐resistant microbiota to alleviate plant abiotic stresses including nutrient deprivation, disease and drought stress (Ab Rahman et al, 2018; Monohon et al, 2021; Olanrewaju et al, 2017; Pieterse et al, 2014; Venturi & Keel, 2016; Vessey, 2003). Identification of stress‐derived metabolome and microbiota constitutes a feasible strategy to deal with abiotic and biotic constraints, however, the beneficial effects of root‐enriched microbial taxa driven by specialized root exudate derived metabolites remain understudied (Hong et al, 2021; Pantigoso, Manter, & Vivanco, 2020; Pantigoso, Yuan, et al, 2020).…”
Section: Plant–microbial Interactions In the Rhizospherementioning
confidence: 99%
“…Previous studies have reported a clear contribution from plant-associated microbial members to plant growth and resilience during drought conditions [30][31][32].…”
Section: Introductionmentioning
confidence: 98%